Lei da alienação parental: um estudo sobre a sua aplicação e eficácia - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2021)
The present work approached the Parental Alienation Law analyzing the proposals of legislative alteration in progress in the national congress. For that, bibliographic research was used as a methodological procedure, carried out in academic google, scielo and bank of theses and dissertations, in addition to information taken from the websites of the courts and the Federal Senate, which made it possible to bring jurisprudential information and the PLs in process. Thus, it was possible to answer the proposed objective of analyzing the legal institute of Parental Alienation regarding its effectiveness. For that, the Parental Alienation (AP) and Law 12,318/2010 were initially addressed, clarifying its historical evolutionary context and social representation, as well as the consequences of the Parental Alienation Syndrome (SAP) and the legal protection provided for in these cases. Next, the procedures and difficulties regarding the application of Law No. 12,318 by the judge were discussed, as well as false accusations and possible solutions to the problem. Finally, the Legislative changes represented in this work by PLS 498/2018, PL 6371/2019, PL 10.712/2018, PL 7352/2017 and PLS 5030/2019 were analyzed. Through the data collected, it was possible to conclude that the LAP is a great achievement in Brazilian law for the protection of the fundamental right of healthy coexistence of minors, but due to several occurrences of misuse of purpose, due to false complaints, difficulties of application, among others, it is not being effective in what it proposed to protect, but its total repeal would be considered a step backwards in the legal regulation and would encourage the harmful practices of the AP, considering its legal helplessness, in this context the bills that aim to revoke both it, when changing it, thus, it was understood that there are several legislative suggestions for its better reformulation, being more prudent the joint analysis of all the proposals so that they are discussed so that they achieve better mechanisms for the protection of children and adolescents.
Keywords: Alienação Parental; Eficácia; Aplicação da lei; Projetos de lei; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS